2017
DOI: 10.3897/natureconservation.17.12251
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in vegetation of a virgin beech woodland remnant: stand-scale stability with intensive fine-scale dynamics governed by stand dynamic events

Abstract: The aim of this resurvey study is to check if herbaceous vegetation on the forest floor exhibits overall stability at the stand-scale in spite of intensive dynamics at the scale of individual plots and stand dynamic events (driven by natural fine scale canopy gap dynamics). In 1996, we sampled a 1.5 ha patch using 0.25 m² plots placed along a 5 m × 5 m grid in the best remnant of central European montane beech woods in Hungary. All species in the herbaceous layer and their cover estimates were recorded. Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
7
0
3
Order By: Relevance
“…The Mátra Mountains (Figure 1) is one of the highest mountain ranges in Hungary, with the highest peak of the country (Kékes, 1014 m a.s.l.). The climate of the region is continental temperate (Standovár et al, 2017) with a mean annual temperature of 5.7°C, while the mean monthly temperature is 15.5°C in July and −4.4°C in January (Ódor, 2000). The annual precipitation is 784 mm at the Kékes meteorological station, the number of snow covered days is 112 (Ódor, 2000).…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mátra Mountains (Figure 1) is one of the highest mountain ranges in Hungary, with the highest peak of the country (Kékes, 1014 m a.s.l.). The climate of the region is continental temperate (Standovár et al, 2017) with a mean annual temperature of 5.7°C, while the mean monthly temperature is 15.5°C in July and −4.4°C in January (Ódor, 2000). The annual precipitation is 784 mm at the Kékes meteorological station, the number of snow covered days is 112 (Ódor, 2000).…”
Section: Regional Settingmentioning
confidence: 99%
“…The bedrock is andesite that is covered by shallow lessivated brown forest soils (Dávid, 1992;Láng et al, 2013). The slope above our coring site is covered by the last primary forests of Hungary, and therefore it is a well-studied and strictly protected area (Kékes Forest Reserve, see in Czájlik, 2009;Standovár et al, 2017). The area below our site has been heavily impacted by human activities: the first evidence of clearings dates back to AD 1856 (see Supplementary Figure 1), when a ca.…”
Section: Regional Settingmentioning
confidence: 99%
“…For example, most parts of the Kékes Forest Reserve (which protects 63 ha of primeval European beech montane forest ecosystem in Hungary) show the characteristic fine-scale mosaic of forest developmental stages sensu Korpel (1995). Standovár ( et al 2017) found the very intensive fine-scale dynamics of the beech forest, determined by natural stand dynamics in this strict forest reserve. The above mentioned authors proved that extinction and colonisation episodes even out at the stand-scale, implying an overall compositional stability of the herbaceous vegetation at the stand-scale after 17 years (whereas the abundance of vegetation changed considerably in relation to the partial closure of the canopy).…”
Section: Introductionmentioning
confidence: 99%
“…Preserved segments of European beech-dominated forests represent valuable natural laboratories (Schultze et al 2014, Standovár et al 2017) that are often incorporated into national ecological networks (Jongman 1995) and international systems of conservation areas, such as the Natura 2000 network (Miko 2012). The high environmental value of these conservation areas requires a multidisciplinary approach to develop and assess forest management plans and policy instruments (Brukas and Sallnäs 2012), to evaluate management regimes (Torres-Rojo et al 2014) and to seek specific forest management alternatives (Götmark 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unmanaged and primary old-growth forests commonly exhibit strong dominance of the closed-canopy developmental stages, with associated low species richness of very specific shade-tolerant and vernal species (Petzold et al, 2018) but with swift development to high abundances of gap-dwelling species in natural disturbance gaps (Naaf & Wulf, 2007;Kelemen et al, 2012). Standovár et al (2017) studied the dynamics of the vegetation in a primary old-growth beech forest in Hungary, focusing on vegetation development in recent and three year old closing gaps. Colonization events and increasing species richness and herbaceous layer cover prevailed in the newly created gaps, but a swift decrease in species richness and herbaceous layer cover, as well as high species turnover, characterized the closing gaps.…”
Section: Non-random Lossesmentioning
confidence: 99%